DETERMINAN AUDIT JUDGMENT (Studi Kasus pada Pemeriksa BPK RI Perwakilan Provinsi Jawa Tengah) - Imelda Adhistya Kusuma Dewi, 13.05.52.0085; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2017)
This study aims to analyze the influence of auditor experience, gender, pressure of obedience, time budget pressure, task complexity, auditor seniority level, and auditors knowledge on audit judgment at BPK RI Auditors of Central Java Province. The population in this study are all examiners who work at the Audit Board (BPK) RI Representative of Central Java. Sampling was counducted using a convenience sampling method and the number of samples were 90 respondents. The primary data retrieval method used is questionnaire method. Data were analyzed using multiple linear regression method. The result of the research shows that auditors knowledge has a significant positive effect on audit judgment, gender and task complexity having a significant negative effect on audit judgment. While the experience of the auditor, the pressure of obedience, the pressure of the time budget, and the degree of auditor seniority have a positive effect is not significant on audit judgment.Keywords: Experience of Auditor, Gender, Pressure of Obedience, Time Budget Pressure, Task Complexity, Degree of Auditor Seniority, Auditors Knowledge, Audit Judgment